Pelaksanaan Supervisi Akademik dalam Meningkatkan Kinerja Guru Madrasah - Jaya, Ariswindra (Yayasan Sembilan Pemuda Indonesia, 2022)
This study aims to describe the implementation of academic supervision in the learning process at MTsN 2 Musi Banyuasin. The method used in this study uses a qualitative descriptive approach with the instrument using an interview guide. Respondents in this study were teachers of MTsN 2 Musi Banyuasin with data collection techniques, namely interviews, observation, and documentation. The results of this study indicate that: (a) academic supervision includes: teacher administration, lesson planning, learning implementation, and learning assessment; (b) no further supervision has been carried out but needs to be further optimized; and (c) the implementation of academic supervision can improve teacher performance in the learning process in madrasah tsanawiyah. This research is expected to contribute to the world of education, especially in the field of implementing supervision strategies in improving teacher performance.